UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA SMP DENGAN PENERAPAN STRATEGI LSQ - SRI TULUS WIJAYANTO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The main key in improving the quality of education is that teachers directly influence, guide and develop the ability of students to become intelligent, skilled and highly moral human beings. Improving the quality of education in schools can be done by applying appropriate and varied strategies, methods and media for each learning concept. However, in reality, not all teachers apply appropriate and varied strategies, methods and media. The learning applied by the teacher is dominated by lectures and the teacher does not stimulate students' thinking, resulting in low student enthusiasm for learning. The low enthusiasm for student learning affects the power of student learning activities in learning. Based on the observations of Class VIIIA SMP Negeri 2 Ngaringan located in Kalanglundo village, Ngaringan sub-district, Grobogan district, it shows that learning interaction in the classroom is relatively low. The lack of variation in learning is caused because teachers are less able to choose strategies and methods that can improve student learning activities in science learning. To increase student interest and student activity in asking questions, an appropriate strategy is needed. One strategy that can foster student interest and activity in learning is the LSQ (Learning Start With a Question) strategy. The strategy is expected to increase student learning activities as indicated by the increase in daily test results on the concept of motion systems in animals and humans. By using the LSQ strategy which is assisted by the group discussion method, it can increase students' enthusiasm for learning and student activity in asking questions and students are active in seeking information. ABSTRAKKunci utama dalam meningkatkan mutu pendidikan adalah para Guru secara langsung mempengaruhi, membimbing dan mengembangkan kemampuan peserta didik agar menjadi manusia yang cerdas, terampil dan bermoral tinggi. Peningkatan mutu pendidikan di sekolah dapat dilakukan dengan menerapkan strategi, metode dan media yang tepat dan bervariasi pada setiap konsep pembelajaran. Namun kenyataannya tidak semua guru menerapkan strategi, metode dan media yang tepat dan bervariasi. Pembelajaran yang diterapkan oleh guru didominasi dengan ceramah dan guru kurang merangsang pemikiran siswa, sehingga mengakibatkan semangat belajar siswa menjadi rendah. Rendahnya semangat belajar siswa mempengaruhi daya aktifitas belajar siswa dalam belajar. Berdasarkan hasil observasi Kelas VIIIA SMP Negeri 2 Ngaringan berlokasi di desa Kalanglundo kecamatan Ngaringan kabupaten Grobogan, Menunjukkan interaksi pembelajaran di dalam kelas relatif rendah. Kurangnya variasi dalam pembelajaran disebabkan karena guru kurang dapat memilih strategi dan metode yang dapat meningkatkan aktifitas belajar siswa dalam pembelajaran IPA. Untuk meningkatkan minat siswa dan keaktifan siswa dalam bertanya diperlukan suatu strategi yang tepat. Salah satu strategi yang dapat menumbuhkan minat dan keaktifan siswa dalam pembelajaran tersebut yaitu strategi LSQ (Learning Start With a Question ). Strategi tersebut diharapkan aktifitas belajar siswa akan meningkat sebagaimana ditunjukkan dengan meningkatnya hasil ulangan harian pada konsep sistem gerak pada hewan dan manusia. Dengan menggunakan strategi LSQ yang dibantu dengan metode diskusi kelompok dapat meningkatkan semangat belajar siswa dan keaktifan siswa dalam bertanya serta siswa aktif dalam mencari informasi.